Addressing vicarious trauma at child welfare professionals - Borjanić-Bolić Emina (Temida, 2018)
This article will discuss vicarious traumatization among child welfare professionals. Vicarious traumatization presents secondary trauma that results from cumulating of clients’ traumatic experiences and has permanent consequences. Secondary trauma among helping professionals is neglected in child welfare system, regardless their day to day work in front lines with deliberately traumatic experiences children and their families were exposed to. Vicarious traumatization is defined by comparison with other related concepts. Likewise, the article describes the signs that indicate the presence of vicarious trauma. Further, the article explains one method in coping Vicarious Trauma manifestation in interrupting phase, before bigger problems occur. Coping in this phase is possible through professional, personal and organizational level. The purpose of this article is to identify the possibilities to overcome vicarious trauma in both helping professionals in child welfare system and other professionals whose work is engaged with traumatized children or youth. If our goal is good quality service, adequate protection of child and youth and their satisfaction with that service, care about child welfare professionals is necessary to prevent vicarious trauma. Beyond professional self-care, it is important that system, organization and managers ensure supportive conditions which will contribute to professional well-being and rising resilience among them.